2010
DOI: 10.1590/s1517-83822010000300018
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of rocks and ectomycorrhizal fungi to promote growth of eucalypt

Abstract: The utilization of rocks as fertilizers is limited by their low solubility. However, solubilization may be achieved by some micro-organisms, such as ectomycorrhizal fungi (ECMf). The aim of this study was to evaluate the potential of seven isolates of ECMf to solubilize two rocks, alkaline breccia and granite, and to liberate potassium and phosphorus for Eucalyptus dunnii seedlings under greenhouse conditions. Fungal inoculants were produced in a peat-vermiculite-liquid medium mixture and added to the planting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 16 publications
0
13
0
6
Order By: Relevance
“…Potassium uptake compared to Mg and Ca was especially enhanced in AM switch grass grown in acid soil (Clark et al 1999). Ectomycorrhizal fungi particularly isolated UFSC-Pt22 and UFSC-Pt186 and contributed to the increase of the efficiency of alkaline breccias as a source of P and K to the plant growth of Eucalyptus dunnii seedlings, respectively (Alves et al 2010). Prajapati et al (2012) reported that potassiumsolubilizing fungi (KSF) strains such as Aspergillus terreus and Aspergillus niger were isolated from various K-rich soil samples and observed that A. terreus and A. niger could solubilize insoluble potassium and showed the highest available potassium in liquid medium by using two various insoluble sources of potassium, i.e., feldspar and potassium aluminum silicate, based on their colonies and morphology characters.…”
Section: Potassium-solubilizing Fungi (Ksf)mentioning
confidence: 98%
See 1 more Smart Citation
“…Potassium uptake compared to Mg and Ca was especially enhanced in AM switch grass grown in acid soil (Clark et al 1999). Ectomycorrhizal fungi particularly isolated UFSC-Pt22 and UFSC-Pt186 and contributed to the increase of the efficiency of alkaline breccias as a source of P and K to the plant growth of Eucalyptus dunnii seedlings, respectively (Alves et al 2010). Prajapati et al (2012) reported that potassiumsolubilizing fungi (KSF) strains such as Aspergillus terreus and Aspergillus niger were isolated from various K-rich soil samples and observed that A. terreus and A. niger could solubilize insoluble potassium and showed the highest available potassium in liquid medium by using two various insoluble sources of potassium, i.e., feldspar and potassium aluminum silicate, based on their colonies and morphology characters.…”
Section: Potassium-solubilizing Fungi (Ksf)mentioning
confidence: 98%
“…The inoculant of the two arbuscular mycorrhizal fungi (AMF) species G. intraradices and G. mosseae were applied in soil on a weight basis and recorded the increasing potassium uptake by maize crop (Wu et al 2005) Information on the uptake of the macronutrient cations through AM plants has been relatively inconsistent in that increases, decreases, and no effects have been reported (Clark and Zeto 1996), and in the case of potassium, it depends on the soil condition as well as nature of plant growth and other conditions (Clark and Zeto 2000). Alves et al (2010) reported that after 90 days, the plant height, root length, shoot dry weight potassium and phosphorus contents, and mycorrhizae colonization were increased in comparison to control. Potassium uptake compared to Mg and Ca was especially enhanced in AM switch grass grown in acid soil (Clark et al 1999).…”
Section: Potassium-solubilizing Fungi (Ksf)mentioning
confidence: 99%
“…The inoculation of the two arbuscular mycorrhizal fungi (AMF) species, G. mosseae and G. intraradices, has been demonstrated to increase the uptake of K by maize crop (Wu et al 2005). Alves et al (2010) reported that the mycorrhizal colonization of Eucalyptus plants improves the plant height, shoot dry weight, root length, and phosphorus and potassium contents as compared to the control. In AM switch grass grown in acid soil, the acquisition of K was especially enhanced (Clark et al 1999).…”
Section: Role Of Mycorrhiza In Potassium Uptake By Plantsmentioning
confidence: 99%
“…In AM switch grass grown in acid soil, the acquisition of K was especially enhanced (Clark et al 1999). In Eucalyptus dunnii seedlings, the ectomycorrhizal fungi increase the efficiency of alkaline breccia as a source of P and K to the seedlings (Alves et al 2010). Ectomycorrhizal fungi actively forage for minerals and act as biosensors that discriminate between different grain sizes and minerals (Leake et al 2008).…”
Section: Role Of Mycorrhiza In Potassium Uptake By Plantsmentioning
confidence: 99%
“…Most tree species create symbiotic relationships with ECM fungi to survive in diverse harsh conditions through an efficient nutrient uptake by ECM fungi (Nara et al 2003;Qu et al 2010;Chorianopoulou et al 2015). For instance, in nutrient impoverished soils, ECM fungi preferentially provide nutrients, like phosphorus (P), and water to the above-ground parts of the host trees rather than the direct absorption by the root tissues (Wallander 2000;Alves et al 2010;Chorianopoulou et al 2015). Therefore, ECM trees absorb more organic P and N than non-ECM trees, since ECM fungi produce ectoenzymes (van der Heijden and Sanders 2002; Choi et al 2005;White and Hammond 2008).…”
Section: Introductionmentioning
confidence: 99%